UTILIZATION OF POWERPOINT SLIDES AS PRESENTATION MEDIA IN THE LEARNING PROCESS - shabillah arca (CV Grasta Glory, 2026)
The rapid development of information and communication technology has brought significant changes to the field of education, especially in the use of digital-based learning media. One of the media widely used in the learning process is Microsoft PowerPoint. This article aims to examine the definition of PowerPoint and its benefits in learning, its strengths and weaknesses, as well as the challenges faced in its implementation within educational environments. The method used in this article is a literature study by collecting various references from books, journals, and relevant previous studies. The results of the study indicate that PowerPoint plays an important role as an interactive learning medium because it can combine text, images, audio, video, animations, and graphics into an attractive and systematic presentation. Proper use of PowerPoint can improve students’ motivation, participation, creativity, and learning outcomes. In addition, PowerPoint supports online and hybrid learning that continues to develop in the digital era. However, the use of PowerPoint also has several weaknesses, such as dependence on technological devices and electricity, limited teacher skills in designing slides, and the risk of ineffective presentation designs that may reduce students’ concentration. Therefore, digital literacy skills, creativity, and a good understanding of presentation design are needed so that PowerPoint can be utilized optimally in creating effective, innovative, and meaningful learning.